CONSUMERS` ATTITUDES TOWARD SOCIAL MEDIA AND TARGETED ADVERTISING IN THE CZECH REPUBLIC - Martin Golob; David Štadáni; Šimon Bolek (Elektronički Zbornik Radova Veleučilišta u Šibeniku)
Social media has tremendously impacted consumers and businesses in the last decade. This relatively new communication channel breaches boundaries year after year in what it can do for its users, no matter the side they are on. Certain benefits can be identified on the consumers` side, but on the business' side as well. Innovation in communicating product and service value using social media evolves very rapidly, with new ways of reaching and gaining the attention of potential consumers being of essential importance. In relation to this, it is valuable to constantly monitor new and emerging consumers` tastes and preferences, not only in products and services they use and buy but in the media and channels they receive information about them. Consumer attitude insights can help social media marketers in developing appropriate social media strategies when marketing their products and services. In this stance, consumers` current attitudes about media, especially social media like the ever-present social networks and advertising techniques that can be used on these networks, is valuable information that can vary across regions, countries, and continents. The aim of this paper was to investigate consumers` attitudes toward social media and targeted advertising in the Czech Republic. The research was conducted on youth and adult population groups regarding their exposure to social media, attitudes regarding the usefulness of social media advertising, buying behaviour, irritation, and targeted advertising. The results show certain differences in age groups that can be useful in tailoring successful marketing strategies on social media.